EFFECT OF OZONE PRETREATMENT ON MICROALGAE HARVESTING AND LIPID EXTRACTION PROCESSES - KADIR, WAN NADIAH AMALINA BINTI KADIR (2019)
Microalgae is identified as the third-generation of biodiesel feedstock with potential to replace current fossil-based diesel. However, harvesting process as well as extraction of lipids are important steps in the overall process to produce microalgae biodiesel as it requires complete dewatering of the biomass which requires high energy input. In the present study, ozone bubble was used as an alternative approach to simultaneously enhance the harvesting process and disrupt the microalgae cells for subsequent biodiesel production. In this study, experimental parameters such as the influence of ozone output dosage (1.84-6.14 g O3/hr), ozonation time (1- 40 min), ozonation flow rate (0.5-8.0 L/min), pH in the sample (5-11) and temperature (24-35°C) were used to study the effects of ozonation pre-treatment on Chlorella vulgaris.